Rn progeny diffusion, deposition and track distribution in diffusion chamber with permeable membrane. (May 2019) - Markovic, V.M.; Markovic, A.G.; Stevanovic, N.; Nikezic, D.
Abstract: Objective of this work is to define method by which sensitivities of CR-39 and LR-115 in diffusion chamber could be determined. Method is based on initial physical processes that occurs in diffusion chamber: diffusion, deposition and decay of radon (isotopes 222 Rn and 220 Rn) and their progeny. Cylindrical shape of chamber was considered due to availability of experimental data for validation of presented method. The shape was not limitation factor and can be extended to any geometry. Diffusion equations for radon in two mediums (membrane and chamber volume) and their progeny in volume were solved using Finite Difference Method – FEM, and solutions are their spatial distributions inside of diffusion chamber. Calculation of flux towards the chamber walls determine distribution pattern and deposited progeny fractions. It has been shown that volume and deposited distributions are not uniform. Visible tracks on CR-39 for defined etching conditions are determined by considering range of alpha particles in air and empirical critical angle function θ C = θ C ( E ) . For LR-115 mean critical angle of 〈 θ c 〉 = 50 0 and energy window from E min = 1.7 MeV to E max = 4.2 MeV was adopted from literature to determine number of visible tracks. The track density distributions on detector are found to be non-uniform and radially dependent. Thickness of permeable membrane has important influence on presence of thoron and its progeny tracks on detector. Sensitivities of CR-39 and LR-115 in diffusion chamber were determined using method presented in this work and compared with other theoretical models and experiment with good agreement. This shown applicability of the presented method. One of important conclusion is that detector sensitivity, given as one simple number, is not the best parameter for calibration due to the existence of radial variation of track density. For cylindrical chamber with 10 cm length and 4 cm radius, covered with membrane in form of one-layer filter paper 0.25 mm thickness, and for equal concentrations of 222 Rn and 220 Rn in front of the chamber, contribution of 220 Rn and its progeny to total track density is about 3%. Highlights: Solution to stationary diffusion of Rn and progeny in diffusion chamber. Determination of volume and deposited fractions of Rn and progeny in chamber. Track density distributions on detector at the bottom of chamber were presented. Model enables determination of detector sensitivity in cylindrical chamber.